Albumin-Stabilized Manganese Oxide/Semiconducting Polymer Nanocomposites for Photothermal-Chemodynamic Therapy of Hepatic Carcinoma - Su, Qi; Liu, Changcun; Zhu, Jingyi; Ding, Mengbin; Zhang, Zhen; Li, Jingchao; Zhang, Qin (Frontiers in Bioengineering and Biotechnology, 2022)
Hepatic carcinoma is one of the most common cancers worldwide, while its treatment remains a great challenge. Traditional therapeutic methods often have disadvantages such as limited therapeutic efficacy and potential side effects. In this study, we report the construction of bovine serum albumin (BSA)–stabilized manganese oxide (MnO2)/semiconducting polymer (SP) nanocomposites to combine photothermal therapy (PTT) and chemodynamic therapy (CDT) for treatment of hepatic carcinoma in living mouse models. Such nanocomposites are composed of BSA, SP, and MnO2 as the stabilizer, PTT, and CDT agent, respectively. SP produced local heat under near-infrared (NIR) laser irradiation for PTT, and MnO2 nanoparticles mediated CDT in the tumor microenvironment, leading to apoptosis of cancer cells. Such nanocomposite-mediated combinational therapy showed a much higher efficacy in inhibiting growth of subcutaneous HepG2 tumors in nude mice than sole treatment. This study thus provides a multifunctional nanoplatform for safe and effective treatment of hepatic carcinoma.